2016
DOI: 10.1097/jcp.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Gambling Associated With Aripiprazole or Dopamine Replacement Therapy

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 75 publications
1
25
0
Order By: Relevance
“…While still controversial, receptor homeostatic compensation is not typically associated with chronic exposure to partial agonists (Varela et al., ; Gao et al., ), and initial reports for aripiprazole promoted this as an attractive feature for long‐term aripiprazole therapy (Burris et al., ). Nonetheless, as reported for full, direct‐acting dopamine agonists (Voon et al., ), ICSD are identified in some patients chronically treated with aripiprazole (Desarkar et al., ; Mouaffak et al., ; Schlachetzki & Langosch, ; Gavaudan et al., ; Kodama & Hamamura, ; Roxanas, ; Cohen et al., ; Smith et al., ; Cheon et al., ; Gaboriau et al., ; Moore et al., ; Bulbena‐Cabre & Bulbena, ; Grall‐Bronnec et al., ; Mahapatra et al., ; Das et al., ; Dhillon et al., ; Etminan et al., ; Gupta et al., ; Mohan et al., ; Peterson & Forlano, ; Reddy et al., ; Lertxundi et al., ). It is noteworthy that these effects may be more frequently associated with higher doses or aripiprazole (Mahapatra et al., ).…”
Section: Functional Neuroanatomymentioning
confidence: 86%
See 1 more Smart Citation
“…While still controversial, receptor homeostatic compensation is not typically associated with chronic exposure to partial agonists (Varela et al., ; Gao et al., ), and initial reports for aripiprazole promoted this as an attractive feature for long‐term aripiprazole therapy (Burris et al., ). Nonetheless, as reported for full, direct‐acting dopamine agonists (Voon et al., ), ICSD are identified in some patients chronically treated with aripiprazole (Desarkar et al., ; Mouaffak et al., ; Schlachetzki & Langosch, ; Gavaudan et al., ; Kodama & Hamamura, ; Roxanas, ; Cohen et al., ; Smith et al., ; Cheon et al., ; Gaboriau et al., ; Moore et al., ; Bulbena‐Cabre & Bulbena, ; Grall‐Bronnec et al., ; Mahapatra et al., ; Das et al., ; Dhillon et al., ; Etminan et al., ; Gupta et al., ; Mohan et al., ; Peterson & Forlano, ; Reddy et al., ; Lertxundi et al., ). It is noteworthy that these effects may be more frequently associated with higher doses or aripiprazole (Mahapatra et al., ).…”
Section: Functional Neuroanatomymentioning
confidence: 86%
“…Nonetheless, as reported for full, direct-acting dopamine agonists (Voon et al, 2017), ICSD are identified in some patients chronically treated with aripiprazole (Desarkar et al, 2007;Mouaffak et al, 2007;Schlachetzki & Langosch, 2008;Gavaudan et al, 2010;Kodama & Hamamura, 2010;Roxanas, 2010;Cohen et al, 2011;Smith et al, 2011;Cheon et al, 2013;Gaboriau et al, 2014;Moore et al, 2014;Bulbena-Cabre & Bulbena, 2016;Grall-Bronnec et al, 2016;Mahapatra et al, 2016;Das et al, 2017;Dhillon et al, 2017;Etminan et al, 2017;Gupta et al, 2017;Mohan et al, 2017;Peterson & Forlano, 2017;Reddy et al, 2017;Lertxundi et al, 2018). It is noteworthy that these effects may be more frequently associated with higher doses or aripiprazole (Mahapatra et al, 2016).…”
Section: The Mystery Of Aripiprazolementioning
confidence: 88%
“…Other studies systematically comparing different dopamine agonists have found no significant difference between each of them (Weintraub et al ., ; Gallagher et al ., ). Recent research also shows a strong effect of aripiprazole, prescribed for the treatment of mood disorders and schizophrenia, with stronger gambling‐related cognition in comparison to other dopamine agonists (Grall‐Bronnec et al ., ).…”
Section: Association With Parkinson's Disease Therapymentioning
confidence: 97%
“…These first cases were considered to be iatrogenic based on chronological and pharmacological arguments: (i) they appeared after the onset of PD and dopamine replacement therapy (DRT) initiation and disappeared after discontinuing DRT; and (ii) DRT acted on dopamine receptors in both the nigrostriatal pathway and the reward pathway, which plays a role in addictive behavior. Several reviews have compiled published case reports or case series [ 8 , 9 ] on this topic. Reported impulsive behaviors were pathological gambling, hypersexuality, compulsive shopping, binge eating, obsessive hobbying, punding, and compulsive medication use.…”
Section: Introductionmentioning
confidence: 99%